AGE AND MOTIVATIONAL INTENSITY IN FOREIGN LANGUAGES LEARNING: A CASE STUDY OF FRENCH LANGUAGE LEARNERS - El-Zine, Nesrine (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Motivation is one of the most researched concepts in the different fields of education, and the field of language learning is certainly not an exception. In the present research, the objective is to examine the Motivational Intensity as being one of the Motivations components. Also, the research investigates the impact, if any, of the factor of age on the examined component. The research addressed the two following questions: To what extent the Yemeni undergraduate learners of the French language are motivated to learn French? Does age have any impact on the degree of motivation of the Yemeni undergraduate learners of French? To answer the researchs questions, a survey was conducted in the Department of French Language and Literature at Sanaa University. The survey was composed of 5 questions that were selected and modified from Gardners AMTB (Attitude, Motivation Test Battery Questionnaire, 1985). The results of the survey demonstrated a statistically high degree of motivational intensity among the Yemeni undergraduate learners of French in general. However, the younger Yemeni learners were more motivated than their older counterparts.